Between Justice and Pragmatism: Operationalizing Islamic Ethics in Indonesia’s Foreign Policy on Palestine - Shahram Akbarzadeh (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2026)
This study explores the integration of Islamic ethical discourse into Indonesian foreign policymaking in relation to Palestine, specifically in responses to the Gaza crisis. It traces Indonesia’s engagement with both normative ideals and pragmatic strategies in domestic and international contexts. Drawing on primary sources, including United Nations (UN) and International Court of Justice (ICJ) statements, this study examines the significance of Islam Wasatiyah (Moderate Islam) and pluralist-democracy for Indonesia’s international standing. This study suggests that Indonesian foreign policy balances ethical idealism and realist statecraft aimed at projecting soft power to the global south and act as a responsible state on the international stage. However, this dual objective presents Jakarta with the risk of a credibility gap as ethical commitments encounter structural barriers and great‑power politics. By examining Indonesia’s Gaza diplomacy, this study offers new insights on how Islamic ethical statecraft can reinforce humanitarian and legal norms while remaining constrained by the very multilateral structures it seeks to humanise.